Efficacy of extracts from cryopreserved placenta on third-degree burns in rats - E. Y. Naumenko; M. I. Shchetinskey; O. M. Bobrova; S. V. Narozhnyi; О. А. Nardid; A. Y. Ulianytska; М. М. Kalashnykova; I. I. Shchetinskaya (Regulatory Mechanisms in Biosystems, 2021)
Human placenta extracts have anti-inflammatory, antioxidant and wound-healing properties, so they are promising drugs for the treatment of wounds of various origins, including burns. Cryopreservation methods are widely used to preserve the biological activity of placental drugs for a long time. The aim of this work was to study the effect of low-temperature storage of the placenta on the regenerative properties of its extracts. Fragments of freshly obtained placentas were cooled by immersion in liquid nitrogen and stored at –196 °C for 6 months. The placenta was warmed in a water bath at 37 °C. The effect of low-temperature preservation of the placenta on the ability of its extracts to positively affect the wound healing process was studied in a model of thermal burn of III B degree in rats. The effectiveness of wound treatment with extracts from cryopreserved placenta was evaluated by planimetric and histological methods at 3, 7, 14, 21 and 28 days after the burn. The activity of antioxidant enzymes in the serum of animals was also determined. superoxide dismutase activity was assessed by inhibition of adrenaline autooxidation in carbonate buffer, catalase activity was assessed by the degree of inhibition of ammonium peroxide formation. It has been shown that the treatment of burns with extracts from cryopreserved placenta helped to accelerate the regeneration processes and the rate of wound healing. The formation of granulation tissue was detected on the 7th day of treatment with extracts, and on the 14th day in the control. The area of burn wounds during treatment with extracts probably differed from the control starting from 14 days after application of the burn. It was found that the dynamics of recovery of catalase activity after burns is probably higher on the 7th day of treatment with extracts. The obtained data testify to the high efficiency of application of placenta stored at low-temperature for the purpose of obtaining extracts from it with preservation of regenerative properties.